1978
DOI: 10.1177/002221947801101005
|View full text |Cite
|
Sign up to set email alerts
|

Why Can't John Read? Perhaps He's Not a Good Listener

Abstract: The relationship between listening comprehension and reading comprehension was investigated. Written and oral comprehension tasks were presented to two groups of readers, matched for IQ and chronological age but differing in their reading ability. The skilledreader group consistently performed better than poor readers in both reading and listening tasks. The results suggest that reading comprehension and listening comprehension are dependent on the same general language processing skills and that poor readers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Additional support for the hypothesis that all readers use phonological information, but that some use it less effectively, comes from a recent article by Booth, MacWhinney, and Perfetti (1999). Their study consisted of presenting second-and sixthgrade children with different nonword primes by flashing the primes on a screen for a duration too brief to allow for complete processing.…”
Section: Phonological Awarenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional support for the hypothesis that all readers use phonological information, but that some use it less effectively, comes from a recent article by Booth, MacWhinney, and Perfetti (1999). Their study consisted of presenting second-and sixthgrade children with different nonword primes by flashing the primes on a screen for a duration too brief to allow for complete processing.…”
Section: Phonological Awarenessmentioning
confidence: 99%
“…In a longitudinal study, Mann and Liberman (1984) found that kindergarten children who would later be more skilled readers outperformed future less skilled readers on a word-string memory task. Listening comprehension problems have also been noted in less skilled readers (Berger, 1978), as have difficulties repeating and comprehending long or complex sentences (Mann, Liberman, & Shankweiler, 1980). On the other hand, less skilled readers perform similarly to more skilled readers on memory tasks that are not recoded phonologically, such as doodles that cannot be recoded as words (Katz et al, 1981), tones (Holmes & McKeever, 1979), and environmental sounds (Brady et al, 1983).…”
Section: Short-term Memorymentioning
confidence: 99%
“…Not surprisingly. listening comprehension problems have also been noted for children with reading disability (e.g.. Berger. 1978;Kotsonis & Patterson.…”
Section: Reading Disability and Difficulties With Language Processingmentioning
confidence: 96%
“…For example, Stanovich (1985) cited studies showing significant correlations between listening comprehension ability and reading skill after third grade. Berger (1978) suggests that students who are struggling to sound out each unfamiliar word may be engaged in behavior that is incompatible with processing the meaning of a message. In addition, Flood and Salus (1982) note that data support a strong relationship between metalinguistic and reading abilities, such as the apparent difficulty poor readers have with anaphoric references (Barnitz, 1980).…”
Section: Awareness Stagementioning
confidence: 99%